Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Produk pada PT Wijaya Safetyndo Gas di Kota Makassar - Syarifuddin Arief; M. Akhyar; M. Dakhri Sanusi; M. Abduh Idris; Maryam Maryam (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the effect of product, price, promotion, and distribution on purchasing decisions at PT Wijaya Safetyndo Gas Makassar. Multiple linear regression analysis was employed to examine the influence of these independent variables on purchasing decisions. The data were analyzed using SPSS version 28. The results indicate that the marketing mix variables—product, price, promotion, and distribution—do not have a statistically significant effect on purchasing decisions, either simultaneously or partially. This is evidenced by the F-test significance value of 0.353 and t-test significance values for all independent variables exceeding the 0.05 threshold. Therefore, it can be concluded that the marketing mix does not significantly influence purchasing decisions at PT Wijaya Safetyndo Gas in Makassar City.